1996
DOI: 10.1073/pnas.93.21.11751
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a superfamily of candidate disease-resistance genes in soybean based on a conserved nucleotide-binding site.

Abstract: The tobacco N and Arabidopsis RPS2 genes, among several recently cloned disease-resistance genes, share a highly conserved structure, a nucleotide-binding site (NBS). Using degenerate oligonucleotide primers for the NBS region of N and RPS2, we have amplified and cloned the NBS sequences from soybean. Each of these PCR-derived NBS clones detected low-or moderate-copy soybean DNA sequences and belongs to 1 of 11 different classes. Sequence analysis showed that all PCR clones encode three motifs (P-loop, kinase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
244
0
13

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(267 citation statements)
references
References 13 publications
8
244
0
13
Order By: Relevance
“…Conservation of several structural motifs within the NBS domain encoded by plant R genes has prompted the development of homology-based approaches aimed at identiWcation of structurally related sequences, termed R gene analogues (RGAs) (Kanazin et al 1996;Yu et al 1996;Leister et al 1996;Aarts et al 1998;Shen et al 1998;Pan et al 2000;van der Linden et al 2004). Cosegregation of speciWc RGAs and R loci and/or quantitative trait loci (QTL) involved in disease resistance has been reported (Hunger et al 2002;Kuhn et al 2003), suggesting that NBS proWling can be a powerful tool for the development of markers linked to resistance loci.…”
Section: Introductionmentioning
confidence: 99%
“…Conservation of several structural motifs within the NBS domain encoded by plant R genes has prompted the development of homology-based approaches aimed at identiWcation of structurally related sequences, termed R gene analogues (RGAs) (Kanazin et al 1996;Yu et al 1996;Leister et al 1996;Aarts et al 1998;Shen et al 1998;Pan et al 2000;van der Linden et al 2004). Cosegregation of speciWc RGAs and R loci and/or quantitative trait loci (QTL) involved in disease resistance has been reported (Hunger et al 2002;Kuhn et al 2003), suggesting that NBS proWling can be a powerful tool for the development of markers linked to resistance loci.…”
Section: Introductionmentioning
confidence: 99%
“…The PCR products were placed into distinct groups and a member of each group was mapped genetically. Altogether, 19 soybean (Kanazin etaL, 1996;Yu et al, 1996) and 12 potato (Leister et al, 1996) sequences were identified and mapped. In each of the three projects, several resistance gene-related fragments mapped near known disease resistance loci.…”
Section: Introductionmentioning
confidence: 99%
“…avenae. Yu et al (1996) identified homologous regions for resistance to obligate biotrophs in Avena, Hordeum and Zea mays on the homologous group 1. The group 1 chromosomes of the Triticeae and the group A chromosomes of oat are homologous to the LG1 of Lolium; on this LG, we also found two QTLs (LpPc2 and LpPc4) linked with crown rust resistance.…”
Section: Synteny At the Marker And Qtl Levelmentioning
confidence: 99%